Analisis Tingkat Kesehatan Unit Simpan Pinjam KUD Mino Saroyo Cilacap - Eka Ambarwati; Khasan Setiaji (Journal of Economic Education and Entrepreneurship Studies, 2021)
The purpose of this study was to analyze the health level of KUD Mino Saroyo 2016-2018 from various aspects. This case study research uses a qualitative approach. Data collection techniques using interviews and documentation. The data analyzed refers to the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and SMEs RI No: 06/Per/Dep/6/IV/2016 concerning guidelines for assessing cooperative health. The results showed that the overall health level of KUD Mino Saroyo Cilacap in 2016-2018 was in the fairly healthy category. This can be seen from the total score, namely in 2016 it got a score of 69.75%, in 2017 it got a score of 70.75%, and in 2018 it got a score of 70.75%. The capital aspect of the ratio of own capital to total assets got the lowest score of 1.50. The quality aspect of earning assets in the risk ratio of non-performing loans to loans in 2016 and 2018 got the lowest score of 1 and in 2017 it got a score of 2. The management aspect has problems in general management and institutional management. The efficiency aspect of the ratio of operating expenses to gross SHU and the ratio of service efficiency got the lowest score. The liquidity aspect of the independence and service ratio got the lowest score of 0. The independence and growth aspect of the service operational independence got a low score of 0. The aspect had a good or high score.